To answer this question, we have:
![(-5x+10)/(-5)](https://img.qammunity.org/2023/formulas/mathematics/college/fh2jdl8snntrzcbh2ti4ca16b5q3t7r486.png)
This is equivalent to the following:
![(-5x)/(-5)+(10)/(-5)](https://img.qammunity.org/2023/formulas/mathematics/college/5fm6du644kebrxvmf3yj3u8q4krqndm961.png)
Then we have:
![\begin{gathered} (-5x)/(-5)=(5x)/(5) \\ (10)/(-5)=-(10)/(5) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4494c7m6m84jx1dcfub7loasyo45ta9x5l.png)
Therefore, we have:
![(5x)/(5)-(10)/(5)](https://img.qammunity.org/2023/formulas/mathematics/college/3zrub6b9wz6o23rvhhoqjoghut4k2asbja.png)
If we simplify both fractions, we finally have:
![\begin{gathered} (5x)/(5)\Rightarrow(5)/(5)=1,(a)/(a)=1 \\ (5x)/(5)=1\cdot x=x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/p88cklgulzjwtqhh0w20ulbku2pt6df53l.png)
And
![-(10)/(5)=-2](https://img.qammunity.org/2023/formulas/mathematics/college/7htgxgkyl6a1j6sb4mydrhmczv70uwcjei.png)
Then after simplification, we finally have:
![\begin{gathered} x-2 \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ww62ddemtp8vecxy457e6v1bn28eqqqd3y.png)
In summary, the process was as follows:
![\begin{gathered} (-5x+10)/(-5)=(-5x)/(-5)+(10)/(-5)=(-5)/(-5)x-(10)/(5)=(5x)/(5)-(10)/(5) \\ (5)/(5)x-(10)/(5)=x-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qmlomsya7bsmujy6c29pjmb44o26b6xn53.png)
The final result is, then, x - 2.